Burkina Faso : Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This annual progress report reviews Burkina Faso's Poverty Reduction Strategy Papers (PRSPs). The regional integration dynamics was considered as an action variable that allowed Burkina Faso to better insert itself into the global economy. The major quantitative objectives of the revised PRSP are to increase per capita GDP by at least 4 percent starting in 2004, to reduce the incidence of poverty to less than 35 percent by 2015, and to increase life expectancy to at least 60 years by 2015. Burkina Faso's performance regarding the implementation of the macroeconomic program remains overall satisfactory.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet